2009 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--5112
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings On Freshmen Engineering Students’ Professional Identity: Implications For Recruitment And Retention

Abstract: Prior to her graduate education, she graduated from the University of Virginia with a B.S. in biology and a B.A. in psychology. She currently serves as a graduate assistant to Dr. Olga Pierrakos working on an NSF funded BRIGE project investigating engineering identity. Olga Pierrakos, James Madison University OLGA PIERRAKOS is an assistant professor in the School of Engineering at James Madison University. Dr. Pierrakos holds a B.S. in Engineering Science and Mechanics, an M.S. in Engineering Mechanics, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…When people perceive a fit between themselves and their environments, they persist longer in those environments [17]- [19]. In engineering, identity is an important factor in people pursuing, persisting, and persevering [16], [20]. Brainard and Carlin's [21] longitudinal study found that freshmen students' identities were better predictors of long-term persistence than even GPAs or self-efficacy.…”
Section: Background: Why Identity Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…When people perceive a fit between themselves and their environments, they persist longer in those environments [17]- [19]. In engineering, identity is an important factor in people pursuing, persisting, and persevering [16], [20]. Brainard and Carlin's [21] longitudinal study found that freshmen students' identities were better predictors of long-term persistence than even GPAs or self-efficacy.…”
Section: Background: Why Identity Mattersmentioning
confidence: 99%
“…Although identity theory has been heavily researched in psychology [4]- [15], [18], [19], [25], it has not been a focus in engineering [16], [20]. Few studies investigate how developing an engineering identity would improve retention of engineering students, especially of women and underrepresented minorities.…”
Section: Background: Why Identity Mattersmentioning
confidence: 99%
“… How closely an individual relates to a particular field, profession, or occupation [6].  The relatively stable and enduring constellation of attributes, beliefs, values, motives and experiences in terms of which people define themselves in a professional role [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…When people perceive a fit between themselves and their fields, they persist longer in those fields [16] - [18]. Hence, identity is a determining factor in one pursuing, persisting, and persevering in engineering [10], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Identities are further derived through associations, affiliations, and identifications with groups [16], [21]. Tonso [22] observes that identity development is an enculturated process where identities are acquired through "community-based interactions" and Beam et al [19] concur that social contexts affect identity. In engineering education, situated learning is central to identity development [22].…”
Section: Introductionmentioning
confidence: 99%